Government Policy on Building Control: legal Aspect - Suseensumpun , Pimuk; Samart, Phasai (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
This research aims to study the government policy on building control in accordance with the Building Control Act, B.E.2522 and amended. Then analyze the said laws to find the appropriate suggestions for legal development. Research methodology used for this research was qualitative research by studying from books, articles, thesis, research reports and related electronic media including in-depth interviews with the local authority. It was found that Thailand has the policies to control buildings through the Building Control Act, B.E.2522 and amended which has the objective to control about the stability of the building, safety of building users, indoor fire protection, public health management and environmental quality preservation, town planning and architecture. But there are some problems with such legal provisions that is the access to information, building demolition condition, legal inconsistencies in case of building moving, the power of the local authority and the mechanism for monitoring the compliance with the law. It was recommended that the Building Control Act, B.E. 2522 should be amended on building demolition, building moving and the power of the local authority to be clear and suitable for enforcement. In addition, the relevant government agencies should have measures to raise awareness and understanding about building control laws that are clear and easy to understand to the public as well as establish mechanisms and proactively working to inspect legal compliance.